Answer:
This is a geometry sequence (I.e each term is found by multiplying the same value to the previous term).
T1 = 4
T2 = -12 = T1 X (-3) = 4 X (-3)
T3 = 36 = T2 X (-3) = 4 X (-3)^2
T4 = 108 = T3 X (-3) = 4 X (-3)^3
The general (explicit) formula for the n-th term of this sequence is:
S(n) = 4 X (-3)^(n-1)
Answer:
its sayin the rectangle answer plus on so
the rec is 3 and the other one is 4
Step-by-step explanation:
Answer:
I'm pretty sure its g(x)
Step-by-step explanation:
The equation of the line that contains (−6, 19) and (−15, 28), in standard form, is: x + y = 13
<em><u>Recall:</u></em>
- Equation of a line can be written in standard from as Ax + By = C, where Ax and By are all terms of variable x and y, and C is a constant.
- The equation of a line in point-slope,
, can be rewritten in the standard form.
- Slope (m) =
![\frac{y_2 - y_1}{x_2 - x_1}](https://tex.z-dn.net/?f=%5Cfrac%7By_2%20-%20y_1%7D%7Bx_2%20-%20x_1%7D)
Given: (−6, 19) and (−15, 28)
<em>Find the </em><em>slope </em><em>(m):</em>
<em />![m = \frac{28 - 19}{-15 -(-6)} = \frac{9}{-9} = -1](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B28%20-%2019%7D%7B-15%20-%28-6%29%7D%20%3D%20%5Cfrac%7B9%7D%7B-9%7D%20%3D%20-1)
Write the equation in point-slope form by substituting m = -1 and
into
.
![y - 19 = -1(x - (-6))\\\\y - 19 = -1(x + 6)](https://tex.z-dn.net/?f=y%20-%2019%20%3D%20-1%28x%20-%20%28-6%29%29%5C%5C%5C%5Cy%20-%2019%20%3D%20-1%28x%20%2B%206%29)
![y - 19 = -1(x + 6)\\\\y - 19 = -x - 6\\\\y = -x - 6 + 19\\\\y = -x + 13\\\\\mathbf{x + y = 13}](https://tex.z-dn.net/?f=y%20-%2019%20%3D%20-1%28x%20%2B%206%29%5C%5C%5C%5Cy%20-%2019%20%3D%20-x%20-%206%5C%5C%5C%5Cy%20%3D%20-x%20-%206%20%2B%2019%5C%5C%5C%5Cy%20%3D%20-x%20%2B%2013%5C%5C%5C%5C%5Cmathbf%7Bx%20%2B%20y%20%3D%2013%7D)
Therefore, the equation of the line that contains (−6, 19) and (−15, 28), in standard form, is: x + y = 13
Learn more about equation of a line in standard form on:
brainly.com/question/19169731
Answer:
what's the question explain pls and I'll answer